PELATIHAN DAN PENYULUHAN PEMANFAATAN POTENSI IKAN BANDENG DESA GUMENO KABUPATEN GRESIK SEBAGAI PRODUK BERNILAI ABON IKAN BANDENG - anggarini, ufafa (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2020)
The community service activities have been done in the form of training and extension of milkfish utilization as potential product from Gumeno Village as Abon Ikan Bandeng (Milkfish Abon). Milkfish as the main commodity in Gumeno was sold at low price especially during harvest time, so the profit of fish farmer is very limited. This community service activities is expected to improve the ability and knowledge of the community about how to process milkfish into abon that contain high nutrition, provide knowledge for for the community how to packing product by promoting hygiene and marketing products through social media. The result that obtained in this activity was the achievement of the economic value of Milkfish Abon and the increase of the ability of housewife who joined in PKK organization in processing, packing, and marketing of their product.